The Dynamics of Prosthetically Elicited Vestibulo-Ocular Reflex Function Across Frequency and Context in the Rhesus Monkey - Phillips, James O.; Ling, Leo; Nowack, Amy L.; Phillips, Christopher M.; Nie, Kaibao; Rubinstein, Jay T. (Frontiers in Neuroscience, 2018)
Electrical vestibular neurostimulation may be a viable tool for modulating vestibular afferent input to restore vestibular function following injury or disease. To do this, such stimulators must provide afferent input that can be readily interpreted by the central nervous system to accurately represent head motion to drive reflexive behavior. Since vestibular afferents have different galvanic sensitivity, and different natural sensitivities to head rotational velocity and acceleration, and electrical stimulation produces aphysiological synchronous activation of multiple afferents, it is difficult to assign apriori an appropriate transformation between head velocity and acceleration and the properties of the electrical stimulus used to drive vestibular reflex function, i.e., biphasic pulse rate or pulse current amplitude. In order to empirically explore the nature of the transformation between vestibular prosthetic stimulation and vestibular reflex behavior, we parametrically varied the pulse rate and current amplitude of constant rate and current amplitude pulse trains, and the modulation frequency of sinusoidally modulated pulse trains that were (frequency modulated, FM) or current amplitude modulated (amplitude modulated, AM). In addition, we examined the effects of differential eye position and head position on the observed eye movement responses. We conclude that there is a strong and idiosyncratic, from canal to canal, effect of modulation frequency on the on the observed eye velocities that are elicited by stimulation. In addition, there is a strong effect of initial eye position and initial head position on the observed responses. These are superimposed on the relationships between pulse frequency or current amplitude and eye velocity that have been shown previously.